2021
DOI: 10.32985/ijeces.12.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Battery energy storage technologies overview

Abstract: Battery technologies overview for energy storage applications in power systems is given. Lead-acid, lithium-ion, nickel-cadmium, nickel-metal hydride, sodium-sulfur and vanadium-redox flow batteries are overviewed. Description, graphical representation, advantages and disadvantages as well as technical characteristics are given for all technologies. Differences and similarities between different battery technologies are perceived. Battery technologies are considered with respect to peak shaving, load leveling,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 29 publications
0
32
0
Order By: Relevance
“…The UPS application serves as an emergency power supply during power outages, where the VRFB system acts as a battery bank that stores electrical energy and supplies it during an emergency. [36] Therefore, rapid response time is a critical property required for this application. In the renewable integration industry, the VRFB technology is mainly used as an energy storage system that is connected with renewable generators, such as wind and solar power generation farms.…”
Section: R E V I E W T H E C H E M I C a L R E C O R Dmentioning
confidence: 99%
“…The UPS application serves as an emergency power supply during power outages, where the VRFB system acts as a battery bank that stores electrical energy and supplies it during an emergency. [36] Therefore, rapid response time is a critical property required for this application. In the renewable integration industry, the VRFB technology is mainly used as an energy storage system that is connected with renewable generators, such as wind and solar power generation farms.…”
Section: R E V I E W T H E C H E M I C a L R E C O R Dmentioning
confidence: 99%
“…Where Qbat is the battery's capacity (Ah), Ebat,max is the maximum amount of energy the battery can store, and V is the battery's nominal voltage (Volt) [24]. The battery power meets the following Equation 8 criteria when it is being charged or discharged.…”
Section: Battery Charge and Dischargementioning
confidence: 99%
“…Batteries are proven options for energy storage applications for residential and commercial use. The authors in [58] presented the comparison of battery technologies and concluded that lithium-ion is currently the most widely used technology, highly suitable for various purposes due to high specific power and energy, high power and energy density, high cell voltage and efficiency between 75% and 97%. The main disadvantage of lithium-ion battery technology is its high price in comparison to other battery technologies [58].…”
Section: Technological Challengesmentioning
confidence: 99%
“…Aggregators rely on storage-type technologies with a less-than-ideal efficiency. Depending on the technology, the efficiency of battery storage is between 50% and 97% [58], while for thermal storage these numbers range from 50% to 90% [78]. Therefore, even though the aggregation of DERs can be useful for achieving RES integration targets, its impact on energy efficiency targets may be the opposite.…”
Section: Environmental Effects Of Aggregatorsmentioning
confidence: 99%